School-Based Mindfulness Enhances Psychological Well-Being in Adolescents after Parental Divorce: A Systematic Review - Slametiningsih; Achir Yani S Hamid; Imami Nur Rachmah; Mustikasari; Raden Irawati Ismail (Universitas Airlangga, 2025)
Background: Adolescents experience various psychosocial challenges, including low self-esteem, depression, substance abuse, and risky behaviors, which adversely affect their psychological well-being. School-based mindfulness interventions have emerged as effective strategies for promoting positive mental health among adolescents. Objective: This systematic review evaluates the effectiveness of school-based mindfulness programs in enhancing psychological well-being in adolescents after parental divorce. Methods: Following PRISMA guidelines, the review analyzed studies identified from nine major databases—Cochrane, Clinical Key, BMC, Medrix, ProQuest, PubMed, Wiley, ScienceDirect, and Taylor & Francis—between February and May 2024. Included studies consisted of randomized controlled trials (RCTs) and quasi-experimental studies focusing on school-based interventions targeting adolescent mental health. The JBI Critical Appraisal Checklist was employed to assess the risk of bias. Results: Out of 757 screened articles, 10 studies involving 27,680 participants from countries including Belgium, Spain, Italy, and Poland were selected. Findings suggest that school-based mindfulness interventions significantly improve psychological well-being and reduce mental health symptoms. Conclusion: Mindfulness-based interventions, when integrated into school environments with consistent support from families and educators, effectively promote psychological well-being among adolescents and reduce mental health risks.